Hidden work in hepatopancreaticobiliary surgery: the contemporary demands of non-operative patient management. Issue 10 (October 2021) - Koea, Jonathan; Srinivasa, Sanket; Leung, Universe; Pimm, Megan; Rodgers, Michael
Abstract: Background: Increasing use is now made of modalities other than surgery (including endoscopy and interventional radiology) in the care of patients with hepatopancreaticobiliary (HPB) diseases. However, the care of and responsibility for patients managed non-operatively continues to reside with surgical services. This investigation was undertaken to quantify the implications of non-operative patient related admissions our HPB unit over a 24 month period. Methods: Total admissions from Jan 2018–Dec 2019 in a tertiary HPB unit were analyzed to determine HPB-related non-operative admissions. Cost analysis was also undertaken. Results: There were 1528 admissions in 1029 patients for non-operative indications out of a total of 2576 admissions to the HPB unit. Of these, 707 were for diagnoses related to underlying HPB or upper gastrointestinal diagnoses. Patients were primarily treated with an interventional radiology procedure (n = 180), diagnostic or therapeutic endoscopy (n = 287), palliation (n = 57), symptomatic management (n = 152), other (n = 31). Patient age ≥80 (p < 0.05), acute admission (p < 0.01) and the presence of a stage 4 cancer diagnosis (p < 0.01) were associated with non-operative admission. Conclusion: Over half of patient admissions are for non-operative management. The contemporary HPB unit is responsible for providing surgical intervention as well as coordinating multidisciplinary care of patients with HPB disease.